№11/(1+v2)+1/(v2+v3)+1/(v3+2)=((v3+2)(v2+v3)+(1+v2)(v3+2)+(v3+v2)(1+v2))/((1+v2)(v2+v3)(v3+2))== (v6+3+2v2+2v3+v3+2+v6+2v2+v3+v6+v2+2)/((v2+v3+2+v6)(v3+2))==(3v6+5v2+4v3+7)/(v6+2v2+3+2v3+2v3+4+3v2+2v6)==(3v6+5v2+4v3+7)/(3v6+5v2+4v3+7)=11/(2-v3)-1/(v3-v2)+1/(v2-1)=((v2-1)(v3--v3)(v2-1)+(2-v3)(v3-v2))/((2-v3)(v3-v2)(v2-1))=(v6-2-v3+v2-2v2+2+v6-v3+2v3-2v2-3+v6)/((2v3-2v2-3+v6)(v2-1))==(3v6-3v2-3)/(2v6-2v3-4+2v2-3v2+3+2v3-v6))=3(v6-v2-1)/(v6-v2-1)=3#2я понял запись так : v(7+4v3+v7+4v3)=v(7+v7+8v3)v(8+2v7-v8-2v7)=v(8-v8)
3x + 4x = 5+1
7x = 6
x = 6/7
2. 2(х+7)=9-2х
2x + 14 = 9 -2x
2x + 2x = 9-14
4x = -5
x = -5/4
3. 3/4(4х+8)=9-(7х-1)
3x + 6 = 9 -7x + 1
3x + 7x = 9 -6+1
10x = 4
x = 4/10 = 2/5